Leaf pigmentation in Cannabis sativa: Characterization of anthocyanin biosynthesis in colorful Cannabis varieties - Kristina K. Gagalova; Yifan Yan; Shumin Wang; Till Matzat; Simone D. Castellarin; Inanc Birol; David Edwards; Mathias Schuetz (Plant Direct)
Abstract Cannabis plants produce a spectrum of secondary metabolites, encompassing cannabinoids and more than 300 non‐cannabinoid compounds. Among these, anthocyanins have important functions in plants and also have well documented health benefits. Anthocyanins are largely responsible for the red/purple color phenotypes in plants. Although some well‐known Cannabis varieties display a wide range of red/purple pigmentation, the genetic underpinnings of anthocyanin biosynthesis have not been well characterized in Cannabis. This study unveils the genetic diversity of anthocyanin biosynthesis genes found in Cannabis, and we characterize the diversity of anthocyanins and related phenolics found in four differently pigmented Cannabis varieties. Our investigation revealed that the genes 4CL, CHS, F3H, F3′H, FLS, DFR, ANS, and OMT exhibited the strongest correlation with anthocyanin accumulation in Cannabis leaves. The results of this study enhance our understanding of the anthocyanin biosynthetic pathway and shed light on the molecular mechanisms governing Cannabis leaf pigmentation.